Housing and Food Insecurity, Health Literacy, and Maladaptive Coping Behaviors - Patrece L. Joseph; Janelle Applewhite; Sasha A. Fleary (SLACK Incorporated, 2022)
Background: Stressors related to social determinants of health (SDH), such as housing and food insecurity, are implicated in chronic disease risk. Maladaptive strategies for coping with these stressors may exacerbate risk. Objective: Given the limited research on SDH-related stressors and maladaptive coping, this study examined the relationship between two SDH-related stressors (housing and food insecurity) and maladaptive coping behaviors (i.e., emotional eating and stress-related cigarette and alcohol use) in adults. Further, because health literacy (HL), another SDH, may be a protective factor, this study explored whether HL moderated these relationships. Methods: Data were collected from adults (N = 500, Mean age = 49.01 years, standard deviation = 16.36; 40% White) in the United States. A series of hierarchical logistic regressions predicting maladaptive coping behaviors from demographics, SDH-related stressors (i.e., housing or food insecurity), and HL variables were estimated. Key Results: Housing insecurity was associated with increased odds of emotional eating (odds ratio [OR] = 1.48, p < .001), stress-related cigarette use (OR = 1.34, p = .001), and stress-related alcohol use (OR = 1.32, p = .001). Food insecurity was associated with increased odds of emotional eating (OR = 1.49, p = .012), stress-related cigarette (OR = 1.68, p = .002), and stress-related alcohol use (OR = 1.49, p = .013). Higher functional HL scores were associated with decreased odds of emotional eating after accounting for housing (OR = 0.79, p = .017) and food insecurity (OR = 0.76, p = .004). Communicative and critical HL moderated the relationship between food insecurity and emotional eating. Conclusions: Examining HL in relation to SDH-related stressors and maladaptive coping behaviors is complex. HL may be less protective for maladaptive coping behaviors that are likely addictive. Because HL domains may require cooperation between individuals and systems related to stressors, multi-systemic interventions are necessary to reduce maladaptive coping behaviors. [HLRP: Health Literacy Research and Practice. 2022;6(4):e280-e289.] Plain language summary: Stress related to inadequate resources for housing and food may be related to adults' poor coping behaviors (e.g., emotional eating and stress-related cigarette and alcohol use). Adults who experienced housing and food insecurity were more likely to report emotional eating and using cigarettes and alcohol when stressed. Adults with higher functional health literacy were less likely to report emotional eating.